Le Nouveau visage de l'euroscepticisme conservateur à la Chambre des Communes - Agnès Alexandre-Collier (Revue Française de Civilisation Britannique)
This article will look at the Conservative MPs who campaigned for Brexit in the run-up to the referendum on 23rd June 2016. After a brief overview of the evolution of the label Euroscepticism and attitudes towards EU membership in the party, it will first try and sketch out the new face of Conservative Euroscepticism in the House of Commons, with a special focus on the 2015 intake of MPs who are supposedly "less pale, male and stale". Through a series of indicators related to parliamentary behaviour, this article will argue that the new Brexiteers are now less dependent on party leadership but more loyal to and representative of their voters. It will finally offer tentative explanations of this new phenomenon, based on party organisational changes which arguably paved the way for the emergence of a new type of Conservative MP. To put it simply, if Euroscepticism has changed within the party, it is essentially because Conservative MPs have radically changed.